2009
DOI: 10.1007/s00580-009-0939-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sialic acid and acute-phase proteins (haptoglobin and serum amyloids A) in healthy and avian infection bronchitis virus-infected chicks

Abstract: Forty-five 24-day-old Cobb chicks infected with infectious bronchitis virus (IBV) and ten healthy 24-day-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
3
20
2
Order By: Relevance
“…These findings are in agreement with recent researches. 21 The concentrations of serum sialic acids showed significant increase in all challenged groups and the highest concentrations were found in the second sampling on day 4 post infection. Main changes were seen in group 1, the group that was inoculated simultaneously with virus and bacteria.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…These findings are in agreement with recent researches. 21 The concentrations of serum sialic acids showed significant increase in all challenged groups and the highest concentrations were found in the second sampling on day 4 post infection. Main changes were seen in group 1, the group that was inoculated simultaneously with virus and bacteria.…”
Section: Discussionmentioning
confidence: 86%
“…In birds, changes in a few acute phase proteins have been described including alpha-1-acid glycoprotein, SAA, transferrin and ovotransferrin. 21,[37][38][39][40] Whicher et al 41 reported an elevation in SAA in all people infected with influenza virus type A and the highest concentrations of ceruloplasmin and SAA were observed on the 3 rd day. It was concluded that SAA measurement could be a valuable indicator in viral infection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Veterinary Biomarker Discovery: Proteomic Analysis of Acute Phase Proteins 191 2.1 Modulation of acute phase proteins during disease in swine Alteration in APP expression has been associated with a number of food animal diseases (Table 1), including mastitis, metritis, and amyloidosis in lactating dairy cattle (Chan et al, 2010;Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2001Eckersall et al, , 2006Takahashi et al, 2006;Grönlund et al, 2003Grönlund et al, , 2005; sepsis, trauma, and respiratory diseases in swine (Amory et al, 2007;Sorensen et al, 2006;Hultén et al, 2003;Heegaard et al, 1998;Eckersall et al, 1996); infectious bronchitis virus in chickens (Nazifi et al, 2011); respiratory diseases in beef cattle (Orro et al, 2011;Heegaard et al, 2000;Godson et al, 1996;Horadagoda et al, 1995); as well as pulmonary damage and caseous lymphadenitis in sheep (Eckersall et al, 2007;Pfeffer and Rogers, 1989 In swine, increased levels of serum HPT have been associated with pathological indications of Mycoplasma hyopneumoniae, a leading cause of porcine enzootic pneumonia (Amory et al, 2007). Similarly, serum concentrations of HPT and SAA were elevated in pigs with experimentally induced Actinobacillus pleuropneumoniae pneumonia Heegaard et al, 1998).…”
Section: Wwwintechopencommentioning
confidence: 99%